2018
DOI: 10.3390/w10091149
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study on the Migration of Heavy Metal Ions in Ice-Water Medium from Ulansuhai Lake

Abstract: Energy is a fundamental driver that causes material movement. It is important to discover changes in energy by studying the internal mechanism of pollutant migration between system components during the freezing process. To explore the migration mechanism of heavy metal ions (HMIs) from ice to water in a lake, we carried out a laboratory freezing experiment and simulated the distribution and migration of HMIs (Fe, Cu, Mn, Zn, Pb, Cd, and Hg) under different conditions. Then, we analyzed the use of energy by fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…In other words, TMn migrated from the ice body to the under-ice water body during the process of water icing. These results were consistent with those of Sun [30], who confirmed the mechanism for the migration of heavy metal ions from ice to water when lakes are freezing from the perspective of energy change. As the thickness of ice increased, the concentration of TMn in the under-ice water body increased continuously, while K continued to decrease, the process of water icing caused the migration of Mn into the under-ice water.…”
Section: Natural Icing Experimentssupporting
confidence: 92%
See 1 more Smart Citation
“…In other words, TMn migrated from the ice body to the under-ice water body during the process of water icing. These results were consistent with those of Sun [30], who confirmed the mechanism for the migration of heavy metal ions from ice to water when lakes are freezing from the perspective of energy change. As the thickness of ice increased, the concentration of TMn in the under-ice water body increased continuously, while K continued to decrease, the process of water icing caused the migration of Mn into the under-ice water.…”
Section: Natural Icing Experimentssupporting
confidence: 92%
“…The TMn content in the water sample was calculated based on the obtained absorbance and calibration curve. For all samples, the concentration of TMn was tested in triplicate, according to the 'Water and Wastewater monitoring analysis method' [29] and Sun's study [30]; the standard deviation of sample test result was controlled within 5%.…”
Section: Natural Icing Experimentsmentioning
confidence: 99%
“…Lake freezing in natural conditions is a macroscopic and complex process, which may influence the translocation of pollutants between solid ice and liquid water in an aquatic system. In order to explore the mechanism for the migration of heavy metal ions (HMIs) from ice to water in a lake, Sun et al [15] carried out a laboratory freezing experiment and simulated the distribution and migration of HMIs (Fe, Cu, Mn, Zn, Pb, Cd, and Hg) under different conditions. The results demonstrated that HMIs could migrate from ice to water as the lake froze, due to the binding energy in water being smaller than that in ice.…”
Section: Background Investigationmentioning
confidence: 99%
“…Міграція полютантів різноманітного походження все ще залишається нагальною проблемою сьогодення (Ren et al, 2010;Nissensohn et al, 2016;Sun et al, 2018). Проблема забруднення стосується як природних водойм, так і водойм штучного походження, серед яких особливої уваги потребують канали, які не тільки виконують функції забезпечення водою посушливих ділянок, а і є місцем існування популяцій гідробіонтів (Khrystenko et al, 2013).…”
Section: вступunclassified